HUBUNGAN DUKUNGAN KELUARGA DENGAN KONSEP DIRI PASIEN KANKER PAYUDA - Lenni Sastra (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2016)
Objective: to analyze the relationship between family support and self-concept of breast cancer patients in outpatient unit Dr. M. Djamil Hospital, Padang, West Sumatra.Methods: This study was an analytic correlation with cross sectional approach. The samples of this study were 73 breast cancer patients taken by using quota sampling technique. Data was collected using questionnaires, and chi-square was used to analyzed the data.Results: 53.4% of breast cancer patients have a negative self-concept. 50.7% get less support from both families. There is a correlation between family support and self-concept in patients with breast cancer.Conclusion: the concept of self-breast cancer patients related to family support. Expected to health workers to encourage families to provide the good support for breast cancer patients with the aim to support the establishment of a positive self-concept.